Support Group WhatsApp Chat Method on Knowledge of Heart Failure Patients at RSUD dr. R. Koesma Tuban - Fauziansyah, Ahmad; Yulian Wiji Utami; Alfrina Hany; Mohammad Fahrul Arifin; Moh. Ubaidillah Faqih (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
Heart failure patients need to gain knowledge of heart failure, one of which is by providing education related to the process of heart failure, its causes and treatment, ways of self-care, how to take medicine, consumption of drinking water and salt intake in food to achieve actual health status. This study aims to determine the effect of group support with the WhatsApp chat method on heart failure patients. This type of research is quasi-experimental, with pretest and posttest control group designs, and it is conducted with a population of 50 patients with heart failure. We had 25 people in the treatment group and 25 people in the control group. Then, the normality test and data analysis were carried out using the Wilcoxon Signed Rank test < 0.05. The results showed that the average respondent was female 33 (66%), farmer occupation 22 (44%), and Killip I functional status was 41 (82%), and the result was p = 0.000 at the level of knowledge of the respondents. From the results of this study, it was concluded that the support group using the WhatsApp chat method can affect knowledge. Still, WhatsApp chat is more appropriate for heart failure patients with higher activities.